The potential of dried and fresh extracts of Sansevieria trifasciata to mitigate Alexandrium tamiyavanichii, a toxic dinoflagellate - Mohammad Noor, Normawaty; Mohd Suberi, Ima Amirah; Susanti, Deny; Mukai, Yukinori; Adam, Aimimuliani; Saad, Shahbudin; Khodzori, Mohd Fikri Akmal (Zibeline International, 2018)
Dinoflagellate is the second largest group of phytoplankton in the marine environment and many of the species have been recognized as toxic species. The high abundance of this species can cause a lot of problems to human health, marine organisms especially caged fish and to the natural environment. In Malaysia, several species of Alexandrium have been reported to cause human intoxication after consumption of contaminated shellfish. During the event, shellfish was banned and lead to economic lost especially to the local fishermen. Therefore, this study was conducted to find alternative way to mitigate the blooms of harmful algae particularly Alexandrium tamiyavanichii using ornamental plant, Sanseviera trifasciata or known as mother-in-law tongue. The extraction of this plant was done in distilled water using dried and fresh plants. Different concentrations of crude extracts (0.001, 0.01, 0.1, 0.5, 1, 1.5, 2 and 2.5 mg/mL) were tested on A. tamiyavanichii within 24 hours. The removal efficiencies (RE) were determined for each concentration tested. The extracts were also tested on brine shrimp to see the possible harmful effect. Results indicate that both extraction methods yielded positive results on A. tamiyavanichii whereby the crude extracts managed to mitigate the species. The LC50 of brine shrimp recorded were 30 mg/ml for fresh plant extract and 70 mg/mL for dried plant extracts. This indicates the possibility of the extractions to be used to mitigate harmful algal bloom (HAB) particularly Alexandrium and provide an alternative way to the relevant agencies to minimize the impact of HAB